2010
DOI: 10.1007/s00391-009-0089-6
|View full text |Cite
|
Sign up to set email alerts
|

Erworbene Kontrakturen der Gelenke im höheren Lebensalter

Abstract: The majority of clinical trials investigating contracture as outcome parameter do not provide a clear definition. However, the success of contracture prevention and treatment in clinical trials and practice can only be judged in the presence of a clear definition. Thus, it appears especially difficult to use contracture as a quality indicator for nursing homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Joint contractures are characterized by restrictions in physiological joint mobility and can even result in immobility [ 1 ]. Joint contractures have a wide range of causes, including immobility, pain, and neurological conditions [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Joint contractures are characterized by restrictions in physiological joint mobility and can even result in immobility [ 1 ]. Joint contractures have a wide range of causes, including immobility, pain, and neurological conditions [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…(4) A recently performed systematic review [15] will be updated and re-analysed to extract categories of the ICF from the outcome measures used.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research has shown that activity limitations and participation restrictions in self-care, mobility or leisure activities are the most relevant aspects from the viewpoint both of older people with contractures living in nursing homes or in the community and of health-care experts [47]. Despite that, the structural impairment in terms of range of motion of the affected joint is still the most frequently reported outcome measure in clinical studies on joint contractures [810]. The number of older individuals affected varies because there is no standardised definition of joint contractures, the diagnostic criteria differ, and settings and populations vary [11].…”
Section: Introductionmentioning
confidence: 99%
“…The first project included the identification of aspects related to functioning and disability of those affected to develop a standardised instrument for assessing the impact of joint contractures [48, 11, 13–17]. Based on the findings of the first project, we developed and piloted the complex intervention Participation Enabling Care in Nursing (PECAN) to improve participation and activities in nursing home residents with joint contractures [10, 18, 19].…”
Section: Introductionmentioning
confidence: 99%